A comparative Study of parenteral versus oral antibiotics in the treatment of severe pneumonia in children under five years of age - Dr. Vasudev Kompally; Dr. K. Vamsi Krishna; Dr. Vijay Kumar G (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction: Pneumonia is a disease known to mankind from antiquity. Pneumonia is an acute inflammation of the pulmonary parenchyma that can be caused by various infective and non-infective origins, presenting with physical and radiological features compatible with pulmonary consolidation of a part or parts of one or both lungs. Objective: This study is aimed to compare parenteral versus oral antibiotics in the treatment of severe pneumonia in children under five years of age. Materials and Methods: This is a prospective observational comparative study. This study was conducted in the department of pediatrics, MGM hospital, Kakatiya Medical College, Warangal. A total of 268 patients were recruited for the study as per the inclusion and exclusion criteria of the WHO guidelines for community acquired pneumonia. Results: A total of 268 children have been enrolled in the present study. Treatment Failure rate in oral amoxicillin group is 12.6% and in Inj. ampicillin plus amikacin group is 11.1%. The difference in treatment outcome in the two treatment groups is NOT statistically significant. A total of 17 out of 134 children in oral amoxicillin group have progressed to treatment failure which amounts to a failure rate of 12.68%. More than half (7/15) of the children who progressed cumulatively to treatment failure in the inj ampicillin plus amikacin group have developed at least one of the signs of WHO defined very severe pneumonia. Conclusion: In the present study it has been observed that there is no statistically significant difference in the failure rate in oral amoxicillin group and Inj. Ampicillin plus Inj. Amikacin group, suggesting similar outcome for severe pneumonia treated with oral amoxicillin and Inj. Ampicillin plus Amikacin.